Persepsi terhadap Training From Senior Student dalam Penugasan Keterampilan Klinik - Oktadoni Saputra; Widyandana Widyandana; Tridjoko Hadianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Peer-Assisted Learning (PAL) has been widely used in medical education. Training From Senior Student (TFSS) is a PAL-scheme program in Skills-Lab FM GMU which one of its aim is to facilitate students to master their cinical skills. However, failure rate in OSCE is still high. This research conducted to explore students’, assistants’ and faculty’s perceptions on the benefits of TFSS in students’ clinical skills acquisition.Method: This study used exploratory focus group discussion (FGD) and in-depth interview with respondents, which were chosen purposively. The data were then transcribed and analysed for themes using deductive content analysis.Results: Thirty-six respondents joined the study (13 medical students; 17 assitants; 6 faculty staffs). The respondents’ perceptions were categorized in 3 aspects: cognitive aspects, social aspects, and organizational aspects of clinical skills learning. As a whole, the view of each respondent was not much differents. TFSS enhanced cognitive and social aspects of both students’ and assistants’ learning, but it didn’t provide the optimal opportunity to practice their skills. Various related problems in organizing were also found.Conclusion: TFSS provided positive benefits on both cognitive and social aspects of clinical skills learning, but not for the opportunity to practice the skills. Improvements need to be done to enhance the quality and quantity of skills training.